2001
DOI: 10.1530/eje.0.1440001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thyrotropin bioactivity in Down's syndrome children with subclinical hypothyroidism

Abstract: Objective: Subclinical hypothyroidism occurs in a number of children with Down's syndrome (DS). The reason for the mildly elevated plasma thyrotropin (TSH) concentrations is not known. The present study investigated whether decreased TSH bioactivity plays a role in this phenomenon. Design: A retrospective study of plasma specimens from DS children with mildly elevated plasma TSH concentrations and thyroid hormone levels within the reference range, using a TSH receptor± adenylate cyclase mediated bioassay. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
0
20
2
3
Order By: Relevance
“…However, Konings and cols. (18) showed normal TSH bioactivity in DS children who had subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 86%
“…However, Konings and cols. (18) showed normal TSH bioactivity in DS children who had subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 86%
“…7,10 Selikowitz 10 pointed out the inappropriate release of TSH resulting from a central dysfunction, production of a less active type of TSH or some form of unresponsiveness of the thyroid gland to TSH as possible explanations for this transient elevation. However, the study carried out by Konings et al 19 showed normal bioactivity of TSH in the plasma of children with DS who had subclinical hypothyroidism. An increased response of TSH to TRH is observed in DS patients.…”
Section: Discussionmentioning
confidence: 91%
“…7,10 Controversy exists over whether such elevation is a risk factor for impaired intellectual outcome in these children 11 and the cause for such elevation has not been clarified yet. [16][17][18][19] Culter et al 2 suggest that the isolated elevation of TSH levels in children with DS, even in the absence of thyroid peroxidase autoantibody (anti-TPO), might be an early sign of primary autoimmune hypothyroidism. Cases with positive anti-TPO are expected to have a frequent progression to overt thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have challenged this hypothesis as proteins involved in mild TSH resistance were normal in patients with Trisomy 21 as well as bioactivity of TSH was normal in children with Trisomy 21 and mildly raised TSH [9]. It has been proposed that these thyroid abnormalities are likely to be thyroidal in origin [10].…”
Section: Introductionmentioning
confidence: 99%